Sifat Mekanik Produk Metalurgi Serbuk dari Proses Ball Milling dengan Bahan Baku Al7075 Terhadap Variasi Temperatur Sinter dan Tekanan Kompaksi - Hizkia Alpha Dewanto; Muhammad Zaini Abdi; Achmad Maulana; Ainun Zulfikar; Gusti Umindya Nur Tajalla (LPPM ITK, 2021)
Powder metallurgy samples, made from Al7075 powder from ball milling, were produced and investigated. Samples were subjected to two different variables, those were compaction pressure and sintering temperatur. Compaction pressure variables were 250, 300, and 350 MPa with constant sintering temperatur of 505oC. Sintering temperatur variations were 425, 465, and 505oC with constant compaction pressure of 350 MPa. The results of density measurement and hardness test were directly proportional to both of research variables, whereas the porosity was inversely proportional. The properties of sample with variables of 350 MPa compaction pressure and 505oC sintering temperatur were the closest one to conventional Al7075, with density of 2.173 g/cm3, 22.2% porosity, and 12.56 VHN hardness. The properties of conventional Al7075 sample were 2.8 g/cm3 density, 0.26% porosity, and 12.68 VHN hardness. The abrupt increase of hardness between 465oC and 505oC sintering temperatur was similar in pattern of its porosity decrease. This means optimum porosity decrease was started between 465oC and 505oC which affecting hardness increase. Highest hardness of powder metallurgy Al7075, which was 99% of conventional Al7075 and porosity of 22.2%, suggested wide application potential of Al7075 produced by powder metallurgy.